2016
DOI: 10.1002/csr.1388
|View full text |Cite|
|
Sign up to set email alerts
|

Testing the Social Innovation Construct: An Empirical Approach to Align Socially Oriented Objectives, Stakeholder Engagement, and Environmental Sustainability

Abstract: Innovation is not just an economic and or technological tool; it is also a social phenomenon. This paper draws together the concepts of creating shared value, the stakeholder theory, and socially oriented innovation to research companies' decisions on asserting socially related objectives when innovating. We examine the extent to which this decision process is bounded by constraints related to information and the characteristics of innovation. To perform this study we used a dataset that monitors the innovatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 53 publications
3
32
0
1
Order By: Relevance
“…R&D spending is often used as a precursor and a determinant of the ability to innovate. If approval and support from stakeholders enhances a firm's performance (Segara-Oña et al, 2016), it is now well-demonstrated that CSR, in particular CP, increases stakeholders' support and legitimacy. Thus investing in CSR and in R&D can be seen as both complementary and competing expenses.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…R&D spending is often used as a precursor and a determinant of the ability to innovate. If approval and support from stakeholders enhances a firm's performance (Segara-Oña et al, 2016), it is now well-demonstrated that CSR, in particular CP, increases stakeholders' support and legitimacy. Thus investing in CSR and in R&D can be seen as both complementary and competing expenses.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…CP is described and perceived as the generous behavior of firms, and generally consists of giving gifts or money to social or charitable causes such as education, health care, disaster relief, and environmental protection (Godfrey, 2005;Wang et al, 2008). It is widely recognized as a useful instrument for firms to build pro-social image and reputation (Godfrey, 2005), and to increase their stakeholder influence capacity (SIC) by cultivating trusting stakeholder relationships (Jones, 1995;Barnett, 2007;Segara-Oña et al, 2016).…”
Section: Linking Cp To Randd: a Curvilinear Relationshipmentioning
confidence: 99%
“…Over the years, social innovation has been widely discussed from various approaches: economic (Mulgan, Tucker, Ali, & Sanders, ), organizational (Phills et al, ; Segarra‐Oña et al, ), and socioecological (Rennings & Rammer, ; Westley & Antadze, ). It has also become a key element for analyzing processes of territorial governance and an instrument for promoting country development (Andrew & Klein, ; Citroni, ; Edwards‐Schachter et al, ; Moulaert, Martinelli, Swyngedouw, & Gonzalez, ).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Social innovation is changing the paradigm for studying innovation. Its impact on society and the concept itself are becoming important and fruitful subjects of research (Avelino et al, ; Cajaiba‐Santana, ; Igarashi & Okada, ; Neumeier, ; Segarra‐Oña, Peiró‐Signes, Albors‐Garrigós, & Miguel‐Molina, ). However, social innovation (SI) is a complex construct that lacks a unifying paradigm in the social sciences (Turker & Altuntas, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation